Perlindungan Hukum Terhadap Identitas Anak Sebagai Pelaku Tindak Pidana Pembunuhan Berencana Pada Pers (Studi Putusan PN Mentok Nomor 2/Pid.Sus-Anak/2023/Pn Mtk) - Maulidah Fitria, Nada; Armanda Agustian, Rio; Arion Hutape, Sintong (CV. Multi Kreasi Media, 2024)
The Mentok District Court ruling No. 2/Pid.Sus-Anak/2023/PN MTK addressed the case of premeditated murder committed by a minor. Legal findings indicated that the child's identity as the perpetrator had been made public in a media article published by a press organization. This study aims to examine the legal protection of a child's identity as the perpetrator of premeditated murder in the press, as well as the criminal responsibility of the press for disclosing the identity of a child who face legal proceeding. The study applies a juridical-normative approach with a focus on case analysis. The findings reveal that the legal protection of a child's identity as the perpetrator of premeditated murder in the press is regulated by several provisions in the Juvenile Criminal Justice System Law and the Child Protection Law. These regulations generally stipulate that the identity of children involved in legal proceedings, whether as perpetrators, victims, or witnesses, must remain confidential. The press entity that publishes the identity of such children can be held accountable for violating children's rights as stipulated in the Child Protection Law. Furthermore, press entity that breaches code of ethics may face criminal sanctions if their actions result in the violation of children's legal rights as outlined in the Juvenile Criminal Justice System Law and the Child Protection Law.